The Relationship Between Microfinance Banks And Sustainable Development In Nigeria: Cointegration Analysis - Najeem Ayodeji Isiaka; Babatunde Bunmi Osifalujo (Garuda Prestasi Nusantara Consulting, 2022)
The debates on why some countries remain underdeveloped have long captured the interest of scholars and researchers with large chunks of these countries populations are still in poverty. Yet with all the attention been paid to sustainable development, the role of microfinance banks is largely ignored. This research work investigated the possible nexus between microfinance banks and sustainable development in Nigeria. It covers the period of 28 years between 1992 and 2018. The secondary data from the Central Bank of Nigeria (CBN) statistical bulletin (2018) was considered in the study. The study employed the Augmented Dickey-Fuller(ADF) Unit Root Test, Co-integration test, Granger Causality test, and multiple regression analysis with aids of ordinary least square method was considered for the empirical findings. It was revealed that there is a long-run relationship between microfinance banks and sustainable development with the test of Johansen co-integration. It was further revealed that there is a unidirectional relationship between MFBI and GDPPC, which means that microfinance banks' investment strongly influences gross domestic product per capita, which represents sustainable development. The study reveals that MFBI and MSP indicate a positive relationship but MFBI is not statistically significant while MSP does have a significant impact on sustainable development in Nigeria. MFBL, MPR, LTDR show a negative relationship and equally posited an insignificant effect on sustainable development in Nigeria. Based on these findings the study concluded that there is a positive relationship between microfinance banks and sustainable development. Therefore, the study recommends among others that monetary authority should strongly equip microfinance banks in Nigeria with the right policy and guidelines that will sustain their existence and, also government should provide enabling environment for them in the rural area to thrive